APLIKASI BAKTERI PELARUT FOSFAT ISOLAT NO. 68 DENGAN BERBAGAI TAKARAN BATUAN FOSFAT PADA MEDIUM GAMBUT DALAM MENINGKATKAN PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Vigna radiata L.) VARIETAS 129 - Aditya, Muhammad; ', Idwar; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to improve the growth and production as well as the interaction of bacteria solvent phosphate and the best dosage of rock phosphate on green beans variety 129 that grown in peat medium. This study was conducted in the area of Jalan Kutilang Sakti Panam, Pekanbaru, from May to November 2012 by using a randomized block design (RAK) factorial. The first factor consists of 2 levels of bacteria solvent phosphate (B), namely: free of bacteria solvent phosphate and granting bacteria solvent phosphate. The second factor is the dosage of rock phosphate (P) in 5 levels i.e; without granting rock phosphate, 0.186 of rock phosphate g/polybag, 0.372 g of rock phosphate/polybag, 0.558 g of rock phosphate/polybag, and 0.744 g of rock phosphate/polybag. Parameters noted were dry weight, root dry weight, the proportion of the pithy pods, the percentage of the total pod, weight of 100 seeds, and harvest seed weight of the green bean plants. Observations results were statistically analyzed by using variance analysis then continued by Duncan's multiple range testson the level 5%. The results showed that, in general, the treatment of bacterial solvent phosphate significantly influenced all of the parameters of the observation. The best combination contained on the combination of bacterial solvent phosphate and dosage 0.744 g of rock phosphate as the best result in crown dry weight, root dry weight, pithy pods percentages total pods percentages, 100 seeds weight, and harvesting seeds weight of green beans plants. Keywords: Green beans, rock phosphate, bacteria solvent phosphate, growth and production.